2018
DOI: 10.3390/molecules23092293
|View full text |Cite
|
Sign up to set email alerts
|

2-Phenylacetamide Isolated from the Seeds of Lepidium apetalum and Its Estrogen-Like Effects In Vitro and In Vivo

Abstract: The aim of this study was to investigate the estrogen-like effects of 2-phenylacetamide (PA), which is the main compound isolated from the seeds of Lepidium apetalum Willd (LA). Results showed that LA and PA could promote the proliferation of MCF-7 cells. The mouse uterine weight test showed that, LA and PA could increase the uterus index of immature female mice, and the levels of luteinizing hormone (LH) and estrogen (E2). LA could increase the expression of ERα and ERβ, while PA could increase the expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…After women enter menopause, poor ovarian reserve, combined with reduced estrogen and increased FSH, lead to postmenopausal obesity, osteoporosis, and perimenopausal syndrome [ 11 , 63 ]. The reduced estrogen action has been clinically associated with obesity, metabolic dysfunction, and increased risk of chronic disease [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…After women enter menopause, poor ovarian reserve, combined with reduced estrogen and increased FSH, lead to postmenopausal obesity, osteoporosis, and perimenopausal syndrome [ 11 , 63 ]. The reduced estrogen action has been clinically associated with obesity, metabolic dysfunction, and increased risk of chronic disease [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The blots were washed five times in TBST, treated for 1 h with IRDyeIgG (1:5000), and washed four times in TBST again. Densitometry analysis was performed as previously described [20].…”
Section: Methodsmentioning
confidence: 99%
“…Estrogen regulates a variety of cell functions through nuclear and non-nuclear signaling pathways or ligand-independent signaling pathways, which can inhibit proliferation of cardiac fibroblasts, hypertrophy and apoptosis of cardiomyocytes, proliferation of vascular endothelial cells and activation of eNOS signal. In our previous studies, it was found that a variety of compounds isolated from traditional Chinese medicine can promote the proliferation of MCF-7 cells and the expression of estrogen receptor [ 20 22 ].…”
Section: Introductionmentioning
confidence: 99%